Chelovek i zakon . Chelovek i zakon . People and the Law . Человек и закон - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Debate on the Constitution; the number of those sentenced to death and other statistics from the Ministry of Justice; the legal status of Russian citizens in Latvia; segment on liberalism as a political theory. Featured in the program: Savitskii, Valerii Mikhailovich (Lawyer) Series description: Socio-political program. Broadcasted since 1974. The program is dedicated to the most important juridical, political, economic, and social issues. The program shows the work of the law enforcement authorities, and does investigative reporting. Дискуссия о Конституции РФ; о количестве приговоренных к смертельной казни и другой статистике Министерства юстиции; о юридическом статусе российских гражданах в Латвии; о политической теории либерализма. В программе участвуют: Савицкий, Валерий Михайлович (Юрист) Описание серии: Общественно-политическая программа. Выходит с 1974 года. Основная тематика программы — важнейшие события в политической, экономической и социальной жизни страны. Выпуски освещают деятельность правоохранительных органов, включают журналистские расследования и разоблачения.